Pore structure and sorption characterization of titanosilicates obtained from concentrated precursors by the sol–gel method. Issue 89 (27th September 2015) - Oleksiienko, O.; Meleshevych, S.; Strelko, V.; Wolkersdorfer, Ch.; Tsyba, M. M.; Kylivnyk, Yu. M.; Levchuk, I.; Sitarz, M.; Sillanpää, M.
<x xml:space="preserve">Abstract</x> Our novel titanosilicate sol–gel synthesis yielded effective sorption materials for Sr2+ and Cs+ decontamination from polluted ground and waste water.